2023
DOI: 10.3233/jpd-225073
|View full text |Cite
|
Sign up to set email alerts
|

Staging Parkinson’s Disease According to the MNCD (Motor/Non-motor/Cognition/Dependency) Classification Correlates with Disease Severity and Quality of Life

Abstract: Background: Recently, a novel simple classification called MNCD, based on 4 axes (Motor; Non-motor; Cognition; Dependency) and 5 stages, has been proposed to classify Parkinson's disease (PD). Objective: Our aim was to apply the MNCD classification in a cohort of PD patients for the first time and also to analyze the correlation with quality of life (QoL) and disease severity. Methods: Data from the baseline visit of PD patients recruited from 35 centers in Spain from the COPPADIS cohort fromJanuary 2016 to No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…Moreover, the present study revealed that a majority of patients were categorized as stage 2 according to the H&Y staging, while most patients fell into stage 3 based on the MNCD classification and staging. Our study also demonstrated positive correlations between PDQ-39 score and both MNCD staging and H&Y staging, with the observed positive correlation between PDQ-39 scores and H&Y staging being consistent with numerous previous studies (Santos-García et al 2023a , b ; Song et al 2014 ; Rahman et al 2008 ). Importantly though, we observed a stronger association between the PDQ-39 total scores and the MNCD staging.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, the present study revealed that a majority of patients were categorized as stage 2 according to the H&Y staging, while most patients fell into stage 3 based on the MNCD classification and staging. Our study also demonstrated positive correlations between PDQ-39 score and both MNCD staging and H&Y staging, with the observed positive correlation between PDQ-39 scores and H&Y staging being consistent with numerous previous studies (Santos-García et al 2023a , b ; Song et al 2014 ; Rahman et al 2008 ). Importantly though, we observed a stronger association between the PDQ-39 total scores and the MNCD staging.…”
Section: Discussionsupporting
confidence: 93%
“…To date, the utilization of the MNCD classification has been limited to a few PD studies (Santos García et al 2021 ; Santos-García et al 2023a , b ), with no existing reports comparing it to the H&Y staging. Our findings in this study demonstrate a stronger correlation between the MNCD classification and the PDQ-39 compared to the H&Y staging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MNCD is based on four major axes (M, motor; N, non‐motor; C, cognition; D, dependency) and proposes five stages, from MNCD stage 1, no relevant symptoms, to MNCD stage 5, dementia and dependency for basic ADL, and a total score from 0 (0 + 0 + 0 + 0 = 0; the best possible status) to 12 (4 + 4 + 2 + 2 = 12; the worst possible status). Recently, we demonstrated using data from the COPPADIS cohort (Santos‐García et al., 2016 , 2019 ) that staging PD with the MNCD classification correlated with disease severity and patients’ QoL (Santos‐García et al., 2023a ). Based on these findings and awaiting the results of an ongoing validation study of the MNCD classification and of its application in a prospective follow‐up cohort, early observations suggest that the MNCD classification could be a useful tool to apply in PD patients to identify the main symptoms of the disease and to monitor the progression of the disorder.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this new analysis was to study the correlation of the MNCD staging with PD caregiver's status. Data from the COPPADIS cohort (Santos‐García et al., 2021a ) used in the previous publication (Santos‐García et al., 2023a ) were used in this analysis. Our hypothesis was that caregivers’ status would be different between the different PD stages according to the MNCD classification, with a better QoL and mood when the patient has a low stage with a low score and vice versa, a worse mood and QoL with greater burden and stress when the patient has a higher stage and score (i.e., a more advanced MNCD stage, a worse caregiver's status).…”
Section: Introductionmentioning
confidence: 99%